American Catholic : the saints and sinners who built America's most powerful church - Morris, Charles R. (New York : Times Books, 1997)
The rise of Catholicism from an insignificant sect in the early nineteenth century to America's largest and most influential Church is a story filled with a cast of immensely colorful characters. Some were great and imposing. Others were comic, a few even shocking and sinister. Charles Morris recounts the rich story of the rise of the Catholic Church in America with an acute eye for the telling detail and the crucial turning points.
American Catholic is not only about the saints and sinners who built the Church, but also the story of how it became the country's dominant cultural force. By the 1950s, no other institution could match its impact on unions, movies, or even popular kitsch. Protestant leaders feared the Church would "Catholicize" the entire nation.
But Catholicism was always as much a culture as a religion, and the Church visibly floundered when the big-city-based Catholic culture suddenly broke down, just about the time John Kennedy became the country's first Catholic president.
The last section of the book explores the Church's continuing struggle to come to terms with secular, pluralist America and the theological, sexual, doctrinal authority, and gender issues that keep tearing it apart. But, surprisingly enough, Morris's grassroots tour - from ultraconservative Lincoln, Nebraska, to more open, experimental dioceses in Saginaw and Seattle - finds Catholicism alive and well, even flourishing, at the parish level.
1. "We Laugh to Scorn" -- 2. God's Own Providential Instrument -- 3. The Whore of Babylon Learns How to Vote -- 4. The Grand American Catholic Compromise -- 5. An American Church -- 6. A Separate Universe -- 7. God's Bricklayer -- 8. On Top of the World -- 9. Stalin, the Pope, and Joe McCarthy -- 10. The End of the Catholic Culture -- 11. Prelude: In a Dark Valley -- 12. At the End of a Century -- 13. Theological Visions -- 14. The Struggle with Sexuality -- 15. Styles, Themes, Dilemmas -- 16. The Church and America.
Includes bibliographical references and index.
Keywords: Catholic Church -- United States -- History -- 19th century; Catholic Church -- United States -- History -- 20th century; United States -- Church history -- 19th century; United States -- Church history -- 20th century